Early Childhood Learning Based on Local Wisdom: A Study of Kindergartens in Pontianak City - Aditya, Farninda; Septian Utut Sugiatno; Siti Nuhalizah; Dara Sa’idah (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study aims to analyze local wisdom-based learning carried out in early childhood at Haruniyah Kindergarten and PKK Benua Melayu Laut Playgroup in Pontianak City. This study uses a qualitative method with a descriptive approach. Data collection through interviews, observations, and documentation. While data analysis through data reduction, data presentation, and drawing conclusions. The results of this study indicate that local wisdom-based learning through various approaches, such as stories and textbooks, has an important role in the formation of character and identity in early childhood. At Haruniyah Kindergarten and PKK Benua Melayu Laut Playgroup, this approach is implemented effectively by integrating local wisdom in learning. The results of this study indicate that in storybooks there is local wisdom content containing elements of local wisdom, such as traditional food and traditional transportation. The book functions as a learning medium that has cultural value